Diplomasi Timor Leste dalam Penyelesaian Sengketa Batas Maritim Laut Timor dengan Australia Tahun 2016 – 2019 - Putri Ade Fitriani (UIR Press, 2023)
The maritime boundary dispute between Timor Leste and Australia is a long-standing issue. Both countries are fighting for their sovereignty and national interests. The dispute occurred because of differences in the basis of international law between the two countries when claiming maritime boundaries in the Timor Sea, which resulted in the absence of a permanent maritime boundary. At that time, Timor Leste claimed based on the UN Convention on the Law of the Sea UNCLOS 1982 while Australia claimed based on the Geneva Convention. There are several diplomatic efforts made by Timor Leste to resolve this dispute, namely through bilateral diplomacy, public diplomacy and also diplomacy through the conciliation process. The purpose of this study is to explain what diplomacy Timor Leste has used to resolve the Timor Sea dispute with Australia. This paper uses a qualitative research method with data collection through literature study. The results of this study show that Timor Leste diplomacy efforts were successful in resolving the maritime boundary dispute case with Australia as marked by the signing of a treaty in 2018 by the two countries that established a permanent maritime boundary in the Timor Sea which has been the cause of the problem between the two countries.